2020
DOI: 10.3390/healthcare8040499
|View full text |Cite
|
Sign up to set email alerts
|

Patient Awareness of Reported Adverse Effects Associated with Proton Pump Inhibitors in a Medically Underserved Community

Abstract: Reports of adverse effects associated with proton pump inhibitors (PPIs) are concerning because of high usage and over-the-counter availability. We sought to determine the awareness of PPI adverse effects among our patient population, which is medically underserved, low-income, and racially diverse. A 21-item survey was administered to gastroenterology-clinic outpatients. It collected information about age, gender, education, race, specialty of the prescriber, specific PPI, indication, knowledge of dose, adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…Our study is consistent with previous studies that showed that GERD/heartburn constituted the majority of indications for PPI prescriptions [ 18 , 19 ]. For example, the participants in another study were mainly prescribed PPIs by gastroenterologists [ 9 ]. Another study reported that most participants were taking PPIs for gastroprotection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study is consistent with previous studies that showed that GERD/heartburn constituted the majority of indications for PPI prescriptions [ 18 , 19 ]. For example, the participants in another study were mainly prescribed PPIs by gastroenterologists [ 9 ]. Another study reported that most participants were taking PPIs for gastroprotection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the most common cause of medication discontinuation was symptom disappearance (71.7%); other causes included fear of side effects (13.1%) and the presence of side effects (5.2%). Another study reported various reasons for PPI discontinuation, including provider's instructions, failure of medication to achieve relief, affordability, and the decision to switch to a different therapy [ 9 ]. In our study, 76.8% of patients who used PPIs reported that the duration of use was as needed, 11.6% were not regular, 4.5% were regular for more than four weeks, 3.6% were regular for less than four weeks, and 3.6% used the medication but did not continue for the recommended duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient dissatisfaction with medication cessation, a lack of symptom control with abrupt discontinuation and the belief that PPIs are a benign class of medications are all reasons found to contribute to the increasing use of PPIs. [18][19][20] However, the long-term use of PPIs has been linked to increased falls and fractures, Clostridioides difficile infections, pneumonia, acute interstitial nephritis, acute kidney injury and electrolyte and micronutrient deficiencies. 11,21 The geriatric population is at greater risk for adverse effects of PPIs due to their inherently higher risk of falls, infections associated with age-related immunosenescence, declining kidney function and polypharmacy.…”
Section: Ryan Dixonmentioning
confidence: 99%